Using Simulations to Integrate Technology into Health Care Aides' Workflow - King, Sharla; Liu, Lili; Stroulia, Eleni; Nikolaidis, Ioanis (International Journal of Advanced Corporate Learning (iJAC), 2013)
Health care aides (HCAs) are critical to home care, providing a range of services to people with chronic conditions, aging or are unable to care for themselves independently. The current HCA supply will not keep up with this increasing demand without fundamental changes in their work environment. One possible solution to some of the workflow challenges and workplace stress of HCAs is hand-held tablet technology. In order to introduce the use of tablets with HCAs, simulations were developed. Once an HCA was comfortable with the tablet, a simulated client was introduced. The HCA interacted with the simulated client and used the tablet applications to assist with providing care. After the simulations, the HCAs participated in a focus group. HCAs completed a survey before and after the tablet training and simulation to determine their perception and acceptance of the tablet. Future deployment and implementation of technologies in home care should be further evaluated for outcomes.